ROLE OF INTRANASAL SPLINTS IN PREVENTING POSTOPERATIVE NASAL MUCOSAL ADHESIONS: Intranasal Splints For Prevention of Nasal Mucosal Adhesion - Maka, Dr Tarique Ahmed; Khan, Zafarullah; Akhtar, Usman; Akram, Bilal; Iqbal, Mubashir (Pakistan Armed Forces Medical Journal, 2018)
Objective: The objective of this study was to compare the efficacy of intranasal splints in the prevention of nasal adhesion following septal surgery. Study Design: Randomized control trial. Place and Duration of Study: Ear, nose and throat (ENT) Department, Combined Military Hospital (CMH) Kharian, from Aug 2014 to Dec 2015. Material and Methods: Patients undergoing septal surgery fulfilling the inclusion criteria were selected. All the patients were randomly allocated a group (A or B) by using the random numbers table. All surgeries were performed by consultant ENT surgeons under general anaesthesia. After septal surgery in group A, both the nostrils were packed with simple nasal packing using vaseline gauze packs. In group B, silastic nasal splint was placed on operated side only and both the nostrils were packed with vaseline gauze packs. Vaseline gauze nasal packs were removed 48 hrs postoperatively. Nasal splint was removed after seven days of surgery. Nasal cavities were inspected for adhesions after 2 weeks from the date of operation. For follow up sconac number of patients was recorded. Results: In our study, out of 234 cases (117 in each group), 57.26% (n=67) in group-A and 53.85% (n=63) in group-B were between 16-30 years of age while 42.74% (n=50) in group-A and 446.15% (n=54) in group-B were between 31-55 years of age, mean ± SD was calculated as 31.45 ± 6.41 and 30.57 ± 4.54 years in group-A and B respectively, 62.39% (n=73) in group-A and 68.38% (n=80) in group-B were male while 37.61% (n=44) in group-A and 31.62% (n=37) in group-B were females, comparison of the efficacy of intranasal splints in the prevention of nasal adhesion following septal surgery was recorded as 86.32% (n=101) in group-A and 96.58% (n=113) in group-B while remaining 13.68% (n=16) in group-A and 3.42% (n=4) developed nasal adhesion. A p-value was calculated as 0.000, showing a significant difference. Conclusion: We concluded that the frequency of efficacy of intranasal splints for the prevention of nasal adhesion following septal surgery is significantly higher when compared with nasal packing.